2020
DOI: 10.3390/cancers12020311
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde Enhances Antimelanoma Activity through Covalently Binding ENO1 and Exhibits a Promoting Effect with Dacarbazine

Abstract: At present, melanoma is a common malignant tumor with the highest mortality rate of all types of skin cancer. Although the first option for treating melanoma is with chemicals, the effects are unsatisfactory and include poor medication response and high resistance. Therefore, developing new medicines or a novel combination approach would be a significant breakthrough. Here, we present cinnamaldehyde (CA) as a potential candidate, which exerted an antitumor effect in melanoma cell lines. Chemical biology method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…There is an increasing number of studies reporting the overexpression of ENO1 in human cancers, making it a candidate for a promising therapeutic and diagnostic target in various types of cancers [ 9 , 41 , 42 ]. Zhang et al [ 43 ] showed that using cinnamaldehyde (an active ingredient that originates from cinnamon) silences ENO1, arrests the cell cycle, and promotes apoptosis of melanoma cells [ 43 ]. The previously discussed ascorbic acid also interacts with ENO1 and induces the apoptosis of melanoma cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing number of studies reporting the overexpression of ENO1 in human cancers, making it a candidate for a promising therapeutic and diagnostic target in various types of cancers [ 9 , 41 , 42 ]. Zhang et al [ 43 ] showed that using cinnamaldehyde (an active ingredient that originates from cinnamon) silences ENO1, arrests the cell cycle, and promotes apoptosis of melanoma cells [ 43 ]. The previously discussed ascorbic acid also interacts with ENO1 and induces the apoptosis of melanoma cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…CETSA was used to detect stability changes in the CYP11B2 protein, according to a previously reported method 28 , 29 . The method is summarized as follows: NCI-H295R cell lysates were treated with AT-I, AT-II, or AT-III (10 μmol/L) for 12 h at different temperatures (37, 40, 43, 46, 49, 52, 55, 58, and 61 °C) or treated with different concentrations of AT-I (0.01, 0.1, 1, 2.5, 5, 10, 20, and 50 μmol/L) for 12 h at 55 °C, and Western blot was used to determine the change in CYP11B2 protein.…”
Section: Methodsmentioning
confidence: 99%
“…The doses were determined according to previous research. [15,27] Nontargeted Metabolomics Analysis: The plasma of cynomolgus macaques was used for nontargeted metabolomics analysis. Nontargeted ultraperformance liquid chromatography (UPLC)-MS/MS analysis and metabolite identification were performed by Shanghai Applied Protein Technology Co., Ltd. (Shanghai, China), who provided technical support and in-depth discussions.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal Shift Assay: This experiment was performed as described in reference [15] with some modifications. Briefly, the ENO1_WT and ENO1_S40 recombinant proteins were exposed to 10 μM CA or PA for 4 h at 37°C.…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation